2012
DOI: 10.1371/journal.pone.0038022
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Increases Serum Fibroblast Growth Factor 21 (FGF21) Levels

Abstract: BackgroundFibroblast growth factor 21 (FGF21) increases glucose uptake. It is unknown if FGF21 serum levels are affected by exercise.Methodology/Principal FindingsThis was a comparative longitudinal study. Anthropometric and biochemical evaluation were carried out before and after a bout of exercise and repeated after two weeks of daily supervised exercise. The study sample was composed of 60 sedentary young healthy women. The mean age was 24±3.7 years old, and the mean BMI was 21.4±7.0 kg/m2. The anthropometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
141
5
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(155 citation statements)
references
References 28 publications
8
141
5
1
Order By: Relevance
“…While 3 months of combined aerobic and resistance exercise diminished FGF21 serum levels [116], 2 months endurance training had no effect on FGF21 serum levels or FGF21 mRNA expression in skeletal muscle [117]. Most interestingly, 2 weeks of daily endurance training and an acute bout of endurance exercise enhanced circulating FGF21 levels and this was accompanied by increased serum levels of NEFA [118,119]. However, in mice, Kim et al observed no increase of Fgf21 mRNA expression in soleus and gastrocnemius muscles and epididymal WAT after an acute bout of exercise, whereas hepatic Fgf21 mRNA expression was significantly enhanced.…”
Section: Key Facts: Myokines As Therapeutic Targetsmentioning
confidence: 95%
“…While 3 months of combined aerobic and resistance exercise diminished FGF21 serum levels [116], 2 months endurance training had no effect on FGF21 serum levels or FGF21 mRNA expression in skeletal muscle [117]. Most interestingly, 2 weeks of daily endurance training and an acute bout of endurance exercise enhanced circulating FGF21 levels and this was accompanied by increased serum levels of NEFA [118,119]. However, in mice, Kim et al observed no increase of Fgf21 mRNA expression in soleus and gastrocnemius muscles and epididymal WAT after an acute bout of exercise, whereas hepatic Fgf21 mRNA expression was significantly enhanced.…”
Section: Key Facts: Myokines As Therapeutic Targetsmentioning
confidence: 95%
“…Accordingly, BAT has been demonstrated as an important source of FGF21 in men. FGF21 and irisin have synergistic effects on WAT browning (132,137).…”
Section: Fibroblast Growth Factor 2 (Fgf2) and Fgf21mentioning
confidence: 99%
“…Acute exercise strongly induces FGF21 expression in both SKM and liver, resulting in increased blood FGF21 (132)(133)(134). However, this response is blunted in obese (135) and T2DM patients (136).…”
Section: Fibroblast Growth Factor 2 (Fgf2) and Fgf21mentioning
confidence: 99%
“…In addition to IL-6, other muscle-secreted proteins such as brain-derived neurotrophic factor, fibroblast growth factor 21, IL-15, and myonectin have been shown to be produced in skeletal muscle in response to acute or chronic exercise, and have been suggested to increase fat oxidation or glucose uptake in skeletal muscles [11][12][13][14][15][16]. A more recent study showed that peroxisome proliferatoractivated receptor gamma coactivator-1 alpha (PGC-1α) expression in skeletal muscle stimulates an increase in Secretory function of skeletal muscle the expression of FNDC5, a membrane protein that is cleaved and secreted as Irisin [17].…”
Section: Metabolic and Immune Functions Of Muscle-secreted Proteinsmentioning
confidence: 99%